Adverse Adolescent Experiences, Psychological Trauma, and the Impact on Management of Educational Learning - Kalogeratos, Gerasimos; Anastasopoulou, Eleni; Tsagri, Angeliki; Tseremegklis, Chrysostomos; Kriparopoulou, Antigoni (Technium Business and Management, 2024)
This study investigates the complex correlation between Adverse Adolescent Experiences (AAEs), psychological trauma, and their subsequent impact on the learning process in adolescents. The primary aim of this study is to understand how traumatic experiences affect essential cognitive functions vital for learning, including memory, concentration, and problem-solving abilities. In educational contexts, we analyze how trauma can present itself, specifically in emotional dysregulation, anxiety, depression, and behavioral issues, all of which can impede academic engagement and success. This study underscores the significance of trauma-informed educational approaches through a comprehensive analysis of existing literature and empirical research. These practices are specifically tailored to acknowledge and address the unique needs of adolescents who have undergone trauma, fostering a safe and supportive learning environment. This study also examines the importance of integrating comprehensive mental health support into educational systems, specifically focusing on how it positively affects affected adolescents’ resilience and academic achievements. Further future implications can provide valuable insights for educators, policymakers, and mental health professionals to develop effective strategies that promote the academic and personal growth of adolescents who have experienced adverse and traumatic events.